The Impact of Self-Efficacy and Social Support Towards Resilience Among Malaysian Working Adults During COVID-19 Pandemic: - - Vadivel, Vinusa; Nainee, Sarvarubini; R. Arumugam, Praveena; Anbalagan, Sujatha (Journal of Techno-Social, 2022)
The drastic economic work stoppage during the coronavirus disease (COVID-19) pandemic has totally impacted many especially the working population. Resilience acts as a protective factor that emphasizes the potential to manage stress and promote wellbeing. In the working environment, resilience is an important asset to be possessed by every individual. Therefore, this study aimed to examine the relationship between self-efficacy, perceived social support, and resiliency among working adults in Malaysia. A total of 184 respondents were recruited using convenience and purposive sampling methods to answer online surveys anonymously. Findings revealed that self-efficacy, support from friends and family showed a positive significant relationship towards resilience while on the contrary, significant others showed a weak relationship. To sum up, results illustrated that self-efficacy was the strongest predictor for resilience among working adults in Malaysia. This research was intended to fill the main gaps in finding the avenues that uphold the resilience attitude among working adults. This study hopes to shed light and serves as a guideline for the policymakers and human resource firms in generating useful schemes to develop the self-efficacy and social support to thrive towards the difficult circumstances successfully among employees in Malaysia.